2022
DOI: 10.3847/1538-4357/ac9b0a
|View full text |Cite
|
Sign up to set email alerts
|

No Peaks without Valleys: The Stable Mass Transfer Channel for Gravitational-wave Sources in Light of the Neutron Star–Black Hole Mass Gap

Abstract: Gravitational-wave (GW) detections are starting to reveal features in the mass distribution of double compact objects. The lower end of the black hole (BH) mass distribution is especially interesting as few formation channels contribute here and because it is more robust against variations in the cosmic star formation than the high-mass end. In this work we explore the stable mass transfer channel for the formation of GW sources with a focus on the low-mass end of the mass distribution. We conduct an extensive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 174 publications
3
17
0
Order By: Relevance
“…The ∼ 10 M peak could also be indicative of particular evolutionary processes that are dominant within formation environments. van Son et al (2022a) showed that a global maximum near this value is consistent and robustly predicted by the stable mass transfer channel in isolated binary evolution, as stability during mass transfer requires mass ratios between the donor star and accreting compact object to be relatively symmetric, and stellar companions to ∼ 10 M BHs must be near this mass to form compact objects above the minimum BH mass. This may be an indication that the stable mass transfer channel operates more efficiently than the traditional common envelope channel for generating merging BBHs.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The ∼ 10 M peak could also be indicative of particular evolutionary processes that are dominant within formation environments. van Son et al (2022a) showed that a global maximum near this value is consistent and robustly predicted by the stable mass transfer channel in isolated binary evolution, as stability during mass transfer requires mass ratios between the donor star and accreting compact object to be relatively symmetric, and stellar companions to ∼ 10 M BHs must be near this mass to form compact objects above the minimum BH mass. This may be an indication that the stable mass transfer channel operates more efficiently than the traditional common envelope channel for generating merging BBHs.…”
Section: Discussionsupporting
confidence: 54%
“…On the high mass end, a sharp decrease in the mass spectrum for black holes with masses 50 M Edelman et al 2021) would be a strong indication that the pair instability process is at play and limiting the core mass of massive stars (Fowler & Hoyle 1964;Barkat et al 1967;Heger & Woosley 2002;Heger et al 2003;Woosley & Heger 2015;Belczynski et al 2016;Woosley 2017Woosley , 2019Marchant et al 2019;Renzo et al 2020), with the location of the decrease in the differential merger rate acting to constrain relevant nuclear reaction rates (Farmer et al 2020). Other overdensities and underdensities in the observed mass distribution Tiwari & Fairhurst 2021;Tiwari 2022;, as well as the evolution of the mass distribution with redshift (Fishbach et al 2021;van Son et al 2022b;Karathanasis et al 2022a;van Son et al 2022a), will further inform the dominant BBH formation channels, binary evolution physics, and the metallicity evolution of the universe.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…) from TNG100.⏬ ✎ 8 https://github.com/TeamCOMPAS/COMPAS 9 We note that the rate in van Son et al (2022b) is slightly higher than the fiducial rate presented in Figure 3 but also in van Son et al (2022a), where more similar settings to this work are used.…”
Section: Optimization Functionmentioning
confidence: 62%
“…The TNG simulations have been shown to match observational constraints on the mass-metallicity relation of galaxies up to z = 2 (Torrey et al 2019), as well as iron abundances (Naiman et al 2018), metallicity gradients within galaxies at low redshift (Hemler et al 2021), and the reduction of star formation in the centers of star-forming galaxies (Nelson et al 2021). Several studies have used the TNG simulations to make predictions for astronomical transient sources (e.g., Bavera et al 2022;Briel et al 2022;van Son et al 2022a). Out of the four Z z , ( ) variations explored, Briel et al (2022) find that TNG provides one of the best agreements between observed and predicted cosmic rates for electromagnetic and GW transients, when combined with their fiducial binary population synthesis model.…”
Section: Illustristng Cosmological Simulationsmentioning
confidence: 99%